Six Years of Running a Campus Open Access Publishing Fund. Where are we? - Otto, Ryan W. (My University, 2019)
How much can $261,000 buy? Around 170 articles, as it turns out. Kansas State University launched an open access publishing fund in 2013 and it has remained active as of the end of the spring semester, 2019. The publishing fund, in short, is a subvention fund used to support the publishing of open access articles by the institution's researchers. K-State is one of many institutions who have launched such funds in the last 10 or so years. Since launching the fund, 221 requests for funding representing 37 different academic departments from around the institution have been reviewed resulting in 173 articles being published in gold open access, with a few more still in process. This poster will assess the K-State Open Access Publishing Fund since the program’s inception in 2013 by providing an overview of the program, the impact of the articles published using a diverse set of research impact metrics, demographics of awardees, compare the data to broader open access publishing trends, and provide conclusions. The assessment will seek to determine if or how well the publishing fund has met its founding four goals and provide a cost-benefit analysis of the program, attempting to answer what did the program accomplish and how much did it cost to do it.
Keywords: Open Access Publishing Fund; KOAPF; Gold Open Access; Scholarly Communication